La lúdica en el fortalecimiento de la expresión oral en los niños de 4 a 5 años de la escuela de Educación Básica Marcos L Durango del recinto Las Cochas parroquia Guanujo, cantón Guaranda, provincia Bolívar, período 2018-2019 - Borja Guzmán, María Elizabeth (2018)
In the present project of intervention carried out in the School Marcos l Durango with the children of initial II the games was an indispensable tool in the strengthening of the oral expression. The child aged 4 to 5 years uses the game as an apprenticeship, but when he arrives at school and they keep him seated at a table without being able to move he causes them to be discouraged and have little interest in learning, the problem we find in the children told us that it was important to work with play to strengthen oral expression because the teacher does not use it as a pedagogical tool but as a break time, so the children do monotonous and boring work without allowing them to play. The teacher does not use the playful as a strategy to develop oral language since the child learns to communicate with the game and by himself, even though the teacher performs activities for the development of oral expression such as recitations, songs but does not use a game during his work; the playful goes hand in hand with the oral expression to develop the ability to express their needs (emotions, ideas, feelings), through oral language. The objective was to develop playful to strengthen oral expression in children through play activities inside and outside the classroom so that the student can develop their language and vocalize better the words, learn new vocabulary, to achieve this we investigate different types of specific games to strengthen the oral expression, in which games with refrains are used to improve communication, we apply the playful with the children to develop the oral language which will also serve the teacher so that she can replicate with other generations. Within the intervention strategies there is the playful as a pedagogical tool to teach children to develop oral language by acquiring new vocabulary and fluency by communicating their emotions feelings and socializing with the rest so that the message of the children reaches everyone, as well Motivating at the moment of working, we constitute ourselves as social beings because we can communicate and in this way access knowledge and enrich our culture feeling confident with ourselves. The process of educational intervention was concluded taking into account the benefits that were acquired with the use of playful adapted to the daily classes and above all allowing to communicate with fluency between children and teacher; the ludic activities with refrains helps to know new words also to a correct pronunciation of the vocabulary where we thus develop the oral language of children who can use words of all the above to serve to develop the oral language and is achieved continuously and repeatedly.